Distribution of Alternaria toxins in tomato pulp and peel and their stability to heat treatments - Giorni, Paola; Barato, Erica; Bertuzzi, Terenzio (Frontiers in Fungal Biology, 2025)
Introduction and methodsThe distribution of tenuazonic acid (TeA), alternariol (AOH), alternariol monomethyl ether (AME), and tentoxin (TEN) between the pulp and peel was determined in different tomato varieties after artificial inoculation with three Alternaria species (Alternaria alternata, Alternaria tenuissima, and Alternaria solani) and incubation for 3 weeks. The role of heat treatments, similar to pasteurization, in their stability was also investigated.Results and discussionUnlike AME that was never detected, TeA, AOH, and TEN were determined at different levels in the pulp and peel. Specifically, AOH remained mainly in the peel, where the inoculation was carried out, while TeA and TEN migrated into the pulp and were also found in the discarded liquid accumulated during the incubation period. Heat treatments reduced TeA, AOH, and TEN to varying degrees. In particular, the TeA level was slightly reduced after treatment both at 100°C (approximately 10%) and 121°C (approximately 20%), while a reduction of approximately 30% was achieved after the double heat treatment (treatment at 100°C followed by treatment at 121°C). AOH was found to be less stable to heat treatments, showing a reduction of around 50% after treatment at 100°C and up to 80% after double heating treatments. TEN was reduced by approximately 50% only after the combined treatment of 100°C + 121°C.